Why Higher Pay Leads to More Crime - Kerry L. Papps (Institute of Labor Economics (IZA), 2025)
The effects on criminal behaviour of raising the minimum wage for those aged 25 and over in the United Kingdom are analysed, using data on police stop and search activities. A 1% increase in the minimum wage raises the fraction of people stopped by the police by 2.96%, the fraction of people caught with an incriminating item by 1.43%, and the fraction of people arrested as a consequence by 1.27%. This effect is almost entirely driven by drug searches made outside business hours, suggesting that the minimum wage raises crime principally by raising disposable income – and drug consumption – among workers.
Keywords: K42; J22; J31; 330; stop and search; crime; minimum wage